Analisis SWOT Sebagai Instrumen Dasar Pengelolaan Madrasah Ibtidaiyah Miftahul Huda Subang - Iyus Tsaury; Mulyawan Sofwandi Nugraha (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
This study aims to analyze the use of the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach as a fundamental instrument in the management of Madrasah Ibtidaiyah (MI) Miftahul Huda Subang in addressing both internal and external institutional dynamics. This research employed a qualitative field research method, with data collected through observation, interviews, and documentation, which were subsequently analyzed using a descriptive-analytical approach. The findings indicate that the madrasah possesses strengths in the form of a strong religious culture and solid community support; however, it still faces weaknesses such as limited facilities and infrastructure and the suboptimal utilization of learning technology. From the external perspective, opportunities include government support and the high public interest in Islamic education, while threats arise from competition with other educational institutions and changes in educational policies. The SWOT analysis proved effective in mapping the internal and external conditions of the madrasah and served as a strategic basis for more directed development planning; therefore, it is recommended that the madrasah continuously optimize the use of learning technology and strengthen collaboration strategies with stakeholders to enhance competitiveness and improve the quality of educational services.